Preventive Efforts and Causal Factors of Traffic Violations Committed by Children: A Case Study of Satlantas Polres Ngawi, 2022-2023 - Bella Dona Mustika Ayu (Fakultas Hukum Universitas Bhayangkara Surabaya, 2026)
This study aims to analyze the preventive efforts undertaken by Satlantas Polres Ngawi in addressing traffic violations committed by children, as well as to identify the underlying causal factors of such violations in Ngawi Regency. The study employs a qualitative case study approach, combining in depth interviews, field observation, and document analysis. Primary data were collected through interviews with seven informants, comprising three Satlantas Polres Ngawi personnel, two teachers from partner schools, and two parent representatives, selected using purposive sampling based on their direct involvement in the preventive programs examined. Data collection was conducted between January and August 2023 and analyzed using the interactive model developed by Miles and Huberman. The findings indicate that Satlantas Polres Ngawi implements five preventive programs, namely school based socialization, collaboration with the Department of Education, data driven violation analysis, social media utilization, and public safety campaigns involving students as safety ambassadors, which theoretically reinforce children's legal awareness and their social control bonds to family, school, and law enforcement. Between January and August, senior high school level accident victims reached 1,252 individuals. Meanwhile, among the twenty identified types of traffic violations, the underlying causes cluster into three principal categories: limited legal awareness and risk perception, inconsistent supervision and law enforcement, and economic and infrastructural constraints. The study concludes that reducing child traffic violations in Ngawi Regency requires continued strengthening of existing educational programs, accompanied by more consistent law enforcement and infrastructure improvement at high risk locations.